The fractured scales : the search for a uniform personal code - Pereira, Faustina (Calcutta : Dhaka : Stree, The University Press, 2002)
With reference to South Asia.
Includes bibliographical references (p. [225]-233) and index.
Keywords: Domestic relations -- Bangladesh; Domestic relations